Introduction to paralegal studies and the law - Edwards, Linda L. (West/Thomson Learning, 2002)
Introduction to Paralegal Studies utilizes a storytelling approach that provides a context in which students can assimilate and organize new concepts. The student is taken from the introduction to the client to the final collection of the judgment in the chronology that would normally occur in litigation. The text explores practical considerations such as docketing timelines, office politics, setting up and organizing files, timekeeping, and asset assessment. Strategic decisions are also explored as they arise naturally in the discovery process, motion practice, trial, and judgment collection. The text contains a number of entertaining forums in which to practice legal terminology and integrate legal concepts, such as "A Trip To The Movies" which provides questions related to popular law-related movies.